A hybrid sectional moment projection method for discrete population balance dynamics involving inception, growth, coagulation and fragmentation. (15th February 2022) - Wu, Shaohua; Yang, Shiliang; Tay, Kun Lin; Yang, Wenming; Jia, Ming
Highlights: A new numerical method for solving the particle population dynamics is presented. This approach has advantages of easy implementation, high accuracy and robustness. It is able to provide the reconstruction of detailed particle size distribution. It is superior to other sectional methods in solving particle fragmentation processes. Abstract: A new and efficient sectional method is developed and presented in this work. This new method, namely hybrid sectional moment projection method, seeks to combine the techniques of moment projection method and sectional method in a flexible and accurate way. It adopts the concept of weighted particles from moment projection method to handle the particle population dynamics. Special treatment is made on the assignment of these weighted particles within each section so that the accumulation of particles at the smallest size can be better described. The performance of hybrid sectional moment projection method has been tested by comparing with the fixed pivot method and conventional sectional quadrature method of moments in handling a number of particle processes including inception, growth, coagulation and fragmentation. Results suggest that the proposed new method is highly robust and accurate. It is able to well predict the evolution of particle population under various conditions. Especially, it is superior to other sectional methods in the treatment of particle fragmentation process.